The Effect of Date (Phoenix dactylifera) Juice on Haemoglobin Level An Experimental Study in Iron Supplemented Rats - Zen, Ady Try Himawan; Pertiwi, Danis; Chodidjah, Chodidjah (Sains Medika : Jurnal Kedokteran dan Kesehatan, 2013)
There has been more research on the iron supplementation. Date juice has been shown to be rich in iron. It has been reported to increase the hemoglobin level in rats. Few studies has been conducted on the effect of date juice on the hemoglobin level in male white Wistar rats fed low iron diet.This research was conducted to evaluate the effect of (Phoenix dactylifera) juice on haemoglobin level in iron supplemented rats. In this experimental study using post test control group design, 24 male white Wistar rats were divided into 4 groups. G-I served as the control group (standard diet and aquadest). G II was given the low Fe diet and aquadest for 21 d. G-III,IV were given the low fe diet and aquadest plus date juice at the concentration of 50%, 100% respectively. The treatment was given for 14 days. Spectrophotometer was used to assess the haemoglobin level of rats. One way anova followed by Post Hoc LSD was applied for the data analysis. Mean of hemoglobin (g/dl) level for the four groups were 12,03, 7.72, 9.25, 10.35 respectively. Test resulted in p<0.05. Post Hoc LSD test resulted in a significant different between K-I and G-II, G-III, G-IV ;G-II and G-III, G-IV ;G-III and G-IV. In conclusion, date juice increases the haemoglobin level in male white rats fed on the low fe diet.